2008
DOI: 10.1038/sj.bjc.6604713
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic impact of NF-κB p105, vimentin, E-cadherin and Par6 expression in epithelial and stromal compartment in non-small-cell lung cancer

Abstract: Vimentin, nuclear factor-kB (NF-kB) p105, fascin, E-cadherin, TGF-b, Par6 and atypical PKC are molecular markers that play an important role in cell differentiation. Herein, we investigate their prognostic impact in primary non-small-cell carcinoma (NSCLC). Tumour tissue samples from 335 resected patients with stage I -IIIA were used. Tissue microarrays were constructed from duplicate cores of both neoplastic cells and stromal cells and were immunohistochemically evaluated. In univariate analyses, high tumour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
104
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(112 citation statements)
references
References 39 publications
4
104
2
2
Order By: Relevance
“…Vimentin has been observed in both stromal cells and cancer cells in breast, lung, and oral cancer (3,(10)(11)(12). Liu et al reported that immunoreactivity of vimentin in cancer cells was associated with tumor progression and worse survival in patients with oral squamous cell carcinomas (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vimentin has been observed in both stromal cells and cancer cells in breast, lung, and oral cancer (3,(10)(11)(12). Liu et al reported that immunoreactivity of vimentin in cancer cells was associated with tumor progression and worse survival in patients with oral squamous cell carcinomas (12).…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, vimentin was detected in both the parenchyma and mesenchyma of various types of cancers, including breast cancer, non-small cell lung cancer, and oral squamous cell carcinoma (7)(8)(9)(10)(11)(12). Vimentin expression in cancer epithelial cells has been associated with metastasis and poor survival (10,12). In gastric cancer, the prognostic value of vimentin remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Although our group has studied more than 100 prognostic markers related to in situ tumor immunology (11,13,14,17,18), angiogenesis (19)(20)(21), and epithelial-mesenchymal transition (22) in NSCLC, stromal CD8 þ score (CD8 þ TIL density in the tumor-related stroma) has been one of the markers with the strongest prognostic impact independent of other clinicopathologic variables including TNM classification. Furthermore, cytotoxic CD8 þ T cells are of increasing interest in lung cancer as novel targeted therapies are aiming to stimulate the immune defense by blocking mechanisms that may inhibit cytotoxic T lymphocytes, e.g., programmed death-1 (PD1), PD-ligand 1 (PD-L1), and cytotoxic T-lymphocyte-associated antigen 4 (CTLA-4; ref.…”
Section: Introductionmentioning
confidence: 99%
“…EMT was also shown to increase cell invasive ability by triggering matrix metalloproteinases (MMPs), such as MMP-2, MMP-3 and MMP-9 (50). In NSCLC, the low vimentin level was found to be a predictor of better survival in primary NSCLC (51). EMT phenotypes in primary cells of lung cancer have been shown to link with anoikis and chemotherapeutic resistance (52,53).…”
Section: Emt and Migratory Suppressionmentioning
confidence: 99%